The Effect of Corporate Governance Mechanism and Company Size on Financial Distress - MUJIYATI, MUJIYATI; ARIANI, KURNIA RINA; PRATAMA, HAFID NUR (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2021)
This study aims to examine the effect of corporate governance mechanisms and company size on the condition of a company experiencing financial distress. The indicators used to measure the corporate governance mechanism in the sample companies are the board of directors, the proportion of independent commissioners, managerial ownership, institutional ownership, and the audit committee. Meanwhile, financial distress is measured using a Springate model. This study uses secondary data from the entire population of mining companies listed on the IDX in 2016-2019. The sampling technique used purposive sampling. The analytical method used is ordinal logistic regression. The results of hypothesis testing show that the board of directors, the proportion of independent commissioners, the audit committee, and company size do not significantly affect the condition of the company experiencing financial distress. Meanwhile, managerial ownership and institutional ownership have a significant effect on companies experiencing financial distress.